To share or not to share? Uncovered losses in a derivatives clearinghouse - Radoslav S. Raykov (Bank of Canada, 2016)
This paper studies how the allocation of residual losses affects trading and welfare in a central counterparty. I compare loss sharing under two loss-allocation mechanisms - variation margin haircutting and cash calls - and study the privately and socially optimal degree of loss sharing. For losses allocated using variation margin haircuts, I find that trading volume is sensitive to the degree of loss sharing and to the risk sensitivity of skinin-the-game capital. By contrast, for cash calls, the degree of loss sharing does not affect trading volume but instead affects the chance that a cash call is honoured, which can constrain the recovery of funds. A welfare analysis characterizes the market outcome and compares it with the social optimum.
Keywords: G19; G21; 330; Economic models; Payment clearing and settlement systems